TRANSFORMASI PENYIARAN DIGITAL URGENSI HARMONISASI REGULASI DALAM ERA MEDIA KONVERGEN STUDI DI KABUPATEN TANAH KARO - Zulham, Zulham; Sazali, Hasan (FIKRUNA: Jurnal Ilmiah Kependidikan dan Kemasyarakatan, 2025)
Digital broadcasting transformation is a must in the context of convergent media that continues to develop. This change not only has a significant impact on broadcasting technology, but also requires regulatory harmonization to ensure that digital broadcasting can be implemented effectively and sustainably. This study aims to analyze the importance of regulatory harmonization in the context of digital broadcasting transformation in Tanah Karo Regency. The methodology used in this study is a qualitative approach with case studies, in-depth interviews, and document analysis. The findings of the study show that there are various challenges in the implementation of digital broadcasting, such as differences in the interpretation of regulations, lack of digital infrastructure, and the need to increase the capacity of human resources. Therefore, harmonization of regulations is crucial to create a consistent framework, encourage innovation, and ensure digital inclusion for all levels of society. This study recommends that local governments collaborate with relevant stakeholders in formulating adaptive and inclusive regulations. In addition, education and training efforts are needed for the public and industry players to maximize the potential of digital broadcasting in the era of convergent media.